Targeting mitochondrial fission as a potential therapeutic for abdominal aortic aneurysm. Issue 3 (8th May 2020) - Cooper, Hannah A; Cicalese, Stephanie; Preston, Kyle J; Kawai, Tatsuo; Okuno, Keisuke; Choi, Eric T; Kasahara, Shingo; Uchida, Haruhito A; Otaka, Nozomu; Scalia, Rosario; Rizzo, Victor; Eguchi, Satoru
Abstract: Aims: Angiotensin II (AngII) is a potential contributor to the development of abdominal aortic aneurysm (AAA). In aortic vascular smooth muscle cells (VSMCs), exposure to AngII induces mitochondrial fission via dynamin-related protein 1 (Drp1). However, pathophysiological relevance of mitochondrial morphology in AngII-associated AAA remains unexplored. Here, we tested the hypothesis that mitochondrial fission is involved in the development of AAA. Methods and results: Immunohistochemistry was performed on human AAA samples and revealed enhanced expression of Drp1. In C57BL6 mice treated with AngII plus β-aminopropionitrile, AAA tissue also showed an increase in Drp1 expression. A mitochondrial fission inhibitor, mdivi1, attenuated AAA size, associated aortic pathology, Drp1 protein induction, and mitochondrial fission but not hypertension in these mice. Moreover, western-blot analysis showed that induction of matrix metalloproteinase-2, which precedes the development of AAA, was blocked by mdivi1. Mdivi1 also reduced the development of AAA in apolipoprotein E-deficient mice infused with AngII. As with mdivi1, Drp1+/− mice treated with AngII plus β-aminopropionitrile showed a decrease in AAA compared to control Drp1+/+ mice. In abdominal aortic VSMCs, AngII induced phosphorylation of Drp1 and mitochondrial fission, the latter of which was attenuated with Drp1 silencing as well as mdivi1. AngII also induced vascular cell adhesion molecule-1 expression and enhanced leucocyte adhesion and mitochondrial oxygen consumption in smooth muscle cells, which were attenuated with mdivi1. Conclusion: These data indicate that Drp1 and mitochondrial fission play salient roles in AAA development, which likely involves mitochondrial dysfunction and inflammatory activation of VSMCs. Graphical Abstract: